Eco-Spiritual Based Green Spirituality : A Systematic Literature Review of Environmentally Conscious Mental Revolution in Education - Supian Ramli; K.A. Rahman; Mohamad Muspawi; Muhammad Sobri; Ady Muh. Zainul Mustofa; Salman Hasani; Nori Nopita Sari (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to provide an understanding of Green Spirituality based on Eco-Spiritual focused on conscious mental revolution environment on education. This research was conducted using the systematic literature review (SLR) method through a qualitative approach, with collecting data from Scopus, Science Direct and Springer. Techniques data analysis used in study was descriptive. The results showed that Eco-spiritual based Green Spirituality that combined spiritual understanding with respect and attention to nature had a connection. It can be seen that Green Spirituality is actually more moderate in its teachings. While the environmental revolution is conscious of education by building spiritual character. Efforts to love the environment must be built and harmonized through real actions starting from society and formal education such as schools and higher education. Implications on study for this guard conscious mental revolution environment that gives vision, inspiration, motivation for environmentalists to construct ethics in the environment education.